Biosafety, biosecurity and antimicrobial resistance containment in Kenya: A One Health scoping review of national and subnational systems - Lazarus Okayo Odeny; Leonard Kingwara; Kennedy Yatich; Benson Ulo; Maureen Kimenye; Jane Owenga (PLOS Global Public Health, 2026)
Antimicrobial resistance (AMR) is a growing global health threat requiring robust biosafety, biosecurity, and surveillance systems across human, animal, and environmental sectors. However, evidence on how these systems function at sub-national and facility levels remains limited, particularly in decentralized settings such as Kenya. This scoping review was conducted in line with PRISMA-ScR reporting standards to map evidence on AMR containment systems in Kenya. Peer-reviewed and grey literature covering governance, surveillance, laboratory capacity, workforce, biosafety and biosecurity, digital systems, and One Health integration between January 2022 - February 2026 were systematically identified and thematically synthesized, with methodological quality assessed using the Mixed Methods Appraisal Tool. A total of 31 studies (23 peer-reviewed and 8 grey literature) were included. Human health systems were the most frequently represented domain (n = 27), followed by data integration and digital platforms (n = 16) and animal health (n = 14). Governance and policy-related components were reported in fewer studies (n = 10), while environmental health was the least represented (n = 8). Despite strong national policies and digital platforms, implementation was uneven across counties and facility levels, with key constraints including workforce shortages, infrastructure gaps, fragmented financing, and limited use of surveillance data. These findings highlight persistent gaps in sub-national implementation and One Health integration that limit the effectiveness of AMR containment systems in Kenya.